Relationship between Airway Anatomical Diameter Variations and Clinical Outcomes of Inhaled Corticosteroids in Asthma - Abdullah Khilji, Nadeem Akhtar Korai, Afshan Abbas, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Asthma is a chronic inflammatory disorder in which airway structure and function vary greatly between individuals. Differences in airway diameter and wall thickness may influence how effectively inhaled corticosteroids (ICS) work, but this relationship is not clearly understood. Objective: This study examined whether natural variations in airway anatomical diameters were associated with the clinical response to ICS therapy in adults with asthma over a one-year period. Methodology: A total of 72 adults with confirmed asthma were enrolled from Khairpur Medical College Hospital, Khairpur Mir's between June 2022 and June 2023. Baseline assessments included spirometry, Asthma Control Test (ACT) scoring, and CT-based measurements of tracheal, bronchial, and segmental airway diameters, as well as wall thickness and wall-area percentage. All participants received standardized ICS therapy and were re-evaluated after one year. Pre- and post-treatment changes were compared, and correlations were used to assess the relationship between airway structure and treatment outcomes. Results: Significant improvement was noted in FEV₁, FVC, the FEV₁/FVC ratio, and ACT scores after one year of ICS use (p < 0.05). Patients with larger airway diameters showed greater improvement in both lung function and symptom control. In contrast, increased airway wall thickness and higher wall-area percentages were associated with weaker treatment responses. Airway diameter groups demonstrated clear differences in ICS responsiveness, with the smallest-diameter group showing the least improvement. Conclusion: Airway anatomical variation appears to be an important determinant of how patients respond to inhaled corticosteroid therapy. Wider airways were linked with stronger clinical improvement, while narrow or remodeled airways predicted a limited response. Structural airway assessment may help guide more individualized asthma management. Keywords: Asthma, Airway diameter, Airway remodeling, Inhaled corticosteroids, Treatment response, Spirometry.